Thai Kratom extracts ameliorate MAFLD through multi-target mechanism in FFA-induced HepG2 cells - Phisit Pouyfung,,, Jonah Bawa Adokwe, Supabhorn Yimthiang,, Ruixue Ma, Tanaporn Khamphaya, (Journal of Applied Pharmaceutical Science, 2025)
Metabolic dysfunction-associated fatty liver disease (MAFLD), characterized by excessive lipid accumulation, is a significant global health concern that is strongly associated with metabolic dysregulation, including insulin resistance and chronic inflammation. Thai kratom (Mitragyna speciosa) extracts exhibit diverse biological activities; however, their effects on hepatic lipid and glucose metabolism in MAFLD remain poorly documented. This study investigated the therapeutic effects of ethanol-extracted red and green kratom and its major alkaloid, mitragynine, in an in vitro MAFLD model using free fatty acid (FFA)-exposed HepG2 cells. Thai Kratom extracts significantly reduced FFA-induced lipid accumulation by activating the AMP-activated protein kinase pathway and downregulating lipogenic enzymes acetyl-CoA carboxylase and fatty acid synthase, key in fatty acid biosynthesis. Thai kratom extract and mitragynine enhanced glycogen production by increasing AKT and GSK3 phosphorylation, reducing precursors for fatty acid synthesis. Additionally, the extract demonstrated anti-inflammatory properties by decreasing p38 MAPK phosphorylation and downregulating key inflammatory mediators (TLR4, c-Jun, CCL2, and CCL21). These results highlight the multifaceted effects of Thai kratom extract and mitragynine on lipid metabolism, insulin signaling, and inflammation, suggesting their potential as therapeutic agents for MAFLD. Future in vivo studies are essential to elucidate the mechanisms of action, paving the way for safe and effective kratom-based MAFLD interventions.
Keywords: Kratom extract (Mitragyna speciosa), MAFLD, Mitragynine